Victims and survivors: Stable isotopes used to identify migrants from the Great Irish Famine to 19th century London. Issue 1 (2nd November 2012) - Beaumont, Julia; Geber, Jonny; Powers, Natasha; Wilson, Andrew; Lee‐Thorp, Julia; Montgomery, Janet
Abstract Historical evidence documents mass migration from Ireland to London during the period of the Great Irish Famine of 1845–52. The rural Irish were reliant on a restricted diet based on potatoes but maize, a C4 plant, was imported from the United States of America in 1846–47 to mitigate against Famine. In London, Irish migrants joined a population with a more varied diet. To investigate and characterize their diet, carbon and nitrogen isotope ratios were obtained from bone collagen of 119 and hair keratin of six individuals from Lukin Street cemetery, Tower Hamlets (1843–54), and bone collagen of 20 individuals from the cemetery at Kilkenny Union Workhouse in Ireland (1847–51). A comparison of the results with other contemporaneous English populations suggests that Londoners may have elevated δ15N compared with their contemporaries in other cities. In comparison, the Irish group have lower δ15N. Hair analysis combined with bone collagen allows the reconstruction of perimortem dietary changes. Three children aged 5–15 years from Kilkenny have bone collagen δ13C values that indicate consumption of maize (C4). As maize was only imported into Ireland in quantity from late 1846 and 1847, these results demonstrate relatively rapid bone collagen turnover in children and highlight the importance of age‐related bone turnover rates, and the impact the age of the individual can have on studies of short‐term dietary change or recent migration. Stable light isotope data in this study are consistent with the epigraphic and documentary evidence for the presence of migrants within the London cemetery. Am J Phys Anthropol, 2013. © 2012 Wiley Periodicals, Inc.